Peran Penyidik Kepolisian dalam Penanganan Tindak Pidana Kekerasan dalam Rumah Tangga - Andi Suhartini; Patahillah Asba; Herman Balla (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This research was conducted with the aim of knowing the role of police investigators in handling criminal acts of domestic violence in Sidenreng Rappang district. And to find out what obstacles are faced by police investigators in handling criminal acts of domestic violence in Sidenreng Rappang district. Type of Research The type of research used in this paper is Normative-Empirical research. The results of the study show that the role of Police Investigators from the Sidenreng Rappang Police in resolving domestic violence crimes in Sidenreng Rappang Regency can be done in two ways, namely through the Family Process (Penal Mediation); and through the legal process (Penal Policy). The Obstacles Faced by Police Investigators in Completing Domestic Violence Crimes in Sidenreng Rappang Regency are Obstacles in Regulations Related to Penal Mediation; Obstacles in the Legal Process; Barriers from the victim; Obstacles From Actors; Barriers from the Family; and Obstacles From the State.